Malay speaker dependent digits recognition with improved backpropagation - Ummu Salamah Mohamad; Ramlan Mahmod; Siti Mariyam Shamsuddin (Penerbit UKM, 2004)
This paper presents a study of a Malay speaker dependent recognition using improved Neural Network (NN). The performances are evaluated for recog-nition of the isolated Malay digits of "0" through "9". The Error Backpropagation (BP) and an improved error signal of the BP are used in this study. Experiments are carried out by comparing the recognition rates and convergence time of the standard BP and improved BP, as well as the effects of normalisation techniques on Malay speaker dependent data. The utter-ances are represented using the Linear Prediction Coding (LPC) method. The results show that the improved BP outperforms the standard BP in terms of its convergence with better recognition rates for unnormalised data. For the effects of normalisation data, the unit simple method gives better result compared to unit range and unit variance with improved BP gives faster convergence and higher recognition rates